The connection between innervation and metabolic rearrangements in pancreatic cancer through serine - Dong, Mengmeng; Cao, Lidong; Cui, Ranji; Xie, Yingjun (Frontiers in Oncology, 2022)
Pancreatic cancer is a kind of aggressive tumor famous for its lethality and intractability, and pancreatic ductal adenocarcinoma is the most common type. Patients with pancreatic cancer often suffer a rapid loss of weight and abdomen neuropathic pain in their early stages. In the advanced stage, cachexia is normally observed in pancreatic cancer patients. The features of patients are considered to be related to metabolic reprogramming of pancreatic cancer which could utilize the nutrition for its own growth through the bypass. Moreover, abundant nerve innervation is responsible for the pain. Recently, with increasing literatures certifying the relationship between nerves and PDAC, the discovery of distinct innervation and anti/pro-tumor functions in PDAC is also increasing. This review aims to unite the innervation and metabolic rearrangements in pancreatic cancer and how it infects its growth and migration. Hopefully, this article could promote some promising measurements for both detection and treatment of pancreatic cancer.